Pelatihan Optimalisasi Facebook untuk Peningkatan Komunikasi antara Masyarakat dan Pemerintah Desa Maukeli - Ignatius Patricio Darma; Yoseph Riang; Maximus Ardon Bidi (Lembaga Pengembangan Kinerja Dosen, 2025)
The process of managing, creating, or organizing something in the best way to achieve the best or ideal results is called optimization. Optimization aims to maximize or minimize certain values ​​to produce effective, successful results consistent with desired goals. You can communicate and interact with people you've never met in person using social media sites like Facebook. Online friendships can even be formed. Social media platforms like Facebook. Social media should be used with caution because almost everyone uses it. Facebook can be used for entertainment, education, promotion, and information sharing, all of which can be beneficial if done correctly. Everyone who uses Facebook should be aware of communication ethics, maintain their privacy, and refrain from sharing offensive content to maintain the security and usability of the platform. The implementation involves socialization methods and question-and-answer sessions with mothers at a social gathering. April 15, 2025. This activity took place at a resident's home. In addition to providing optimization training, the activity also aimed to improve communication between the village head and residents through the active involvement of participants. The goal was also to create a positive discussion atmosphere to improve community well-being and foster a stronger sense of togetherness and trust for future village growth. This will allow for identification of existing communication barriers and collaborative work to find solutions.